2021
DOI: 10.1111/nph.17544
|View full text |Cite
|
Sign up to set email alerts
|

CaADIP1‐dependent CaADIK1‐kinase activation is required for abscisic acid signalling and drought stress response in Capsicum annuum

Abstract: Summary Induction of the abscisic acid (ABA) signalling network is associated with various stress conditions, including cold, high salinity and drought. As core ABA signalling components, group A type 2C protein phosphatases (PP2Cs) interact with and inhibit snf1‐related protein kinase2s. Here, we isolated and characterised the pepper mitogen‐activated protein kinase kinase kinase CaADIK1, which interacts with the group A PP2C CaADIP1. CaADIK1 transcripts were induced by abiotic stresses, and CaADIK1 localis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 64 publications
(97 reference statements)
0
18
0
Order By: Relevance
“…We have previously demonstrated that the kinase activity of CaADIK1, a homolog of CaMEKK23, contributes to ABA and drought stress responses (Jeong et al ., 2021), and thus, we predicted that drought stress‐promoted CaMEKK23 kinase activity might be closely associated with the enhanced drought tolerance and ABA sensitivity of CaMEKK23 ‐OX plants. To verify this assumption, we generated transgenic Arabidopsis plants overexpressing the kinase activity deficient CaMEKK23 K32N mutant (Figs 6, S3C), which were then exposed to drought stress.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…We have previously demonstrated that the kinase activity of CaADIK1, a homolog of CaMEKK23, contributes to ABA and drought stress responses (Jeong et al ., 2021), and thus, we predicted that drought stress‐promoted CaMEKK23 kinase activity might be closely associated with the enhanced drought tolerance and ABA sensitivity of CaMEKK23 ‐OX plants. To verify this assumption, we generated transgenic Arabidopsis plants overexpressing the kinase activity deficient CaMEKK23 K32N mutant (Figs 6, S3C), which were then exposed to drought stress.…”
Section: Resultsmentioning
confidence: 94%
“…This identical function tends to limit the scope of VIGS in elucidating differences between the influence of these two genes on pepper plant phenotypes. As an alternative approach to assess the putative association between CaSnRK2.6 and CaMEKK23, we adopted a strategy based on our findings that CaADIK1, a homolog of CaMEKK23, interacts with and is inhibited by CaADIP1, a group A PP2C (Jeong et al ., 2021). Specifically, we pondered as to whether CaMEKK23 might interact with pepper PP2Cs including CaADIP1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For in vitro phosphorylation analyses, we used kinase buffer (1 mM CaCl 2 , 1 mM dithiothreitol, 2.5 mM MnCl 2 , 2.5 mM MgCl 2 , and 20 mM Tris-HCl, at pH 7.5) and 15 lCi [c-32 P]-ATP, with assays being performed using a previously described protocol (Jeong et al, 2020(Jeong et al, , 2021Kim et al, 2021).…”
Section: Phosphorylation Assaysmentioning
confidence: 99%